2019
DOI: 10.3390/ijms20205120
|View full text |Cite
|
Sign up to set email alerts
|

Using Transcriptome Analysis to Screen for Key Genes and Pathways Related to Cytoplasmic Male Sterility in Cotton (Gossypium hirsutum L.)

Abstract: Cotton (Gossypium hirsutum L.) is one of the most important cash crops worldwide. Cytoplasmic male sterility (CMS) is an excellent breeding system for exploitation of heterosis, which has great potential to increase crop yields. To understand the molecular mechanism of CMS in cotton, we compared transcriptome, cytomorphological, physiological and bioinformatics data between the CMS line C2P5A and its maintainer line C2P5B. By using high-throughput sequencing technology, 178,166 transcripts were assembled and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 126 publications
1
18
0
Order By: Relevance
“…This demonstrates that a ROS burst may occur during anther development in the CMS-D2 line ZBA. This finding is consistent with other cotton sterile lines, such as Zhong41A (CMS-D8) [9] and C2P5A [24]. A decrease in ATP but excessive ROS accumulation was found in a transformant expressing the rice CMS-associated gene orfH79 [89].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This demonstrates that a ROS burst may occur during anther development in the CMS-D2 line ZBA. This finding is consistent with other cotton sterile lines, such as Zhong41A (CMS-D8) [9] and C2P5A [24]. A decrease in ATP but excessive ROS accumulation was found in a transformant expressing the rice CMS-associated gene orfH79 [89].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, numerous differentially expressed genes (DEGs) were identified in the CMS line H276A ( Gossypium barbadense L.) through a comparative transcriptome analysis, most of which were associated with energy-related metabolic pathways (e.g., the tricarboxylic acid (TCA) cycle, respiratory electron transfer, and oxidative phosphorylation), pentatricopeptide repeat (PPR) proteins, and MYB (v-myb avian myeloblastosis vira I oncogene homolog) transcription factors [11]. Recently, transcriptome sequencing was also used to investigate the cotton CMS line C2P5A, which revealed that genes associated with ROS detoxification enzymes, tapetum proteins, transcription factors, vital metabolic pathways including starch and sucrose metabolism, galactose metabolism, ascorbate and aldarate metabolism, glutathione metabolism, and pyruvate metabolism were differentially expressed in anthers [24]. Although some cotton mitochondrial genomes have been reported so far [25,26], relatively little progress has been achieved in terms of CMS-associated genes in cotton.…”
Section: Introductionmentioning
confidence: 99%
“…The main abortion stages of the Jin A cotton CMS line are the sporogenic cell and microspore mother cell, and the main characteristic is that the sporogenic cells cannot divide normally [ 44 ]. Pollen abortion for the cotton CMS lines H276A [ 22 ], LD6A [ 25 ], and C2P5A [ 27 ] occurs at the tetrad stage. Pollen abortion for the cotton CMS line J4A evaluated in the present study occurred during meiosis in the microspore mother cell stage, as the tapetum cells did not undergo programmed cell apoptosis during the entire developmental process, and the anthers ultimately had an insufficient energy supply and underwent abortion.…”
Section: Discussionmentioning
confidence: 99%
“…Altered metabolic pathways influence the biological processes leading to CMS [ 7 ]. With the development of the technology for high-throughput sequencing and bioinformatics, CMS-related genes are discovered through the construction of transcription regulatory networks, which are related to the tricarboxylic acid (TCA) cycle, oxidative phosphorylation, respiratory electron transport chain, toxic proteins, and carbohydrate metabolism [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Besides, miRNA also plays an important role in flower development in plants [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the molecular mechanisms controlling anther development and male sterility is of great importance for heterosis utilization in many crop species, including cotton. In recent years, male sterility lines have been widely studied by transcriptomic analysis in different species, such as wheat [56,57], maize [58], eggplant [59] and cotton [60][61][62][63]. However, most studies tend to carry out extensive enrichment of DEGs without systematic classi cation analysis based on different development stages.…”
Section: Discussionmentioning
confidence: 99%